THE EFFICACY OF DUTASTERIDE AND GREEN TEA TOWARDS BLEEDING ON BPH AFTER TURP: STUDY THEIR EFFECT ON HIF-1α EXPRESSION & HEMATOCRIT - Irawan, Andry; Riwanto, Ignatius; Nugroho, Eriawan Agung (Indonesian Urological Association, 2017)
Objective: This study proves differentiation of the combination of dutasteride and green tea, dutasteride, green tea, and placebo alone and their association with differences in hematocrit levels and the expression of hypoxia induced factor-1 alpha (HIF-1α) in patients with Benign Prostate Hyperplasia (BPH) were performed Trans urethral resection of the prostate (TURP) surgery. Material & method: Experimental study with the draft